Exploring the preferred teaching styles of adult learners in an institute of teacher education in Malaysia / Norzalina Abdul Rashid - Abdul Rashid, Norzalina (2012)
This case study aims to identify the teaching styles preferred by the adult learners. It also investigates the dominant teaching styles of the lecturers as perceived by the learners. Comparisons between the preference for and the perception of the learners with respect to the lecturers' teaching styles were made to determine any significant difference. The teaching styles employed for this study were based on Grasha's Model (1996) which consisted of five styles which are the Expert, Formal Authority, Personal Model, Facilitator and Delegator teaching styles. The survey method uses the 5-point Likert Scale questionnaire as the instrument to collect data. The data collected was analysed using SPSS. Descriptive statistics such as frequency, mean and standard deviation were used to describe the respondents' preferences for and perceptions of the lecturers' teaching styles. Meanwhile, t-tests were used to analyse the difference between the preferences for and perceptions. The samples were selected through the nonprobability convenience sampling. They were 44 TESL students from the GSTT Foundation Programme who were currently in the first semester and 2 lecturers from the Language Development component. Analysis of the data showed that the three most preferred teaching styles of the adult learners were the Facilitator, Personal Model and the Expert teaching style respectively. It was also found that the three most dominant teaching styles of the lecturers as perceived by the learners were the Facilitator, Expert and the Personal Model style. There were no significant difference between the learners' preferred teaching styles and the perceived teaching styles of the lecturers for all the styles except for the Personal Model. Findings of this study is consistent with the Cluster 3 combination of Grasha * s Model which consists of the Expert, Personal Model and the Facilitator style. The increasing number of adult learners initiated this study in which the teaching styles that work best for these learners will be identified. It will further enable educators to ensure that active learning takes place through the process of teaching and learning. Recommendations to study students' attitude and level of motivation are suggested to further ensure active learning takes place as these are some of the contributing factors that affect the teaching and learning process in the classroom.